Analisis Tingkat Prioritas Atribut Kualitas Layanan Perusahaan Penyedia Jasa Layanan Logistik - Moh Farid Najib (Business Administration Department - Universitas Katolik Parahyangan, 2012)
This study specifically have the purpose is to define the attributes of service qual-ity; determine the strengths and weaknesses of the quality of service; categorizingstrengths and weaknesses of the quality of service firms engaged in logistics servicesprovider. The depth Interview with servqual model framework as well as logisticsservice quality model was conducted to define the attributes of logistics serviceproviders. This sample size was 200 respondents, and of the 258 questionnairesdistributed and returned by 25 of which can be processed as many as 201 respondents.32 items defined and analyzed using a model servqual to determine the strengths andweaknesses of the quality of service, categorization strengths and weaknesses andtesting performed by using Paired sample t-test it was found that the weighting isperformed so that the resulting ranking of the attributes of the service.Keywords: SERVQUAL, Logistics Service Provider